2014
DOI: 10.1016/j.cej.2014.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton oxidation of catechol and 4-chlorocatechol catalyzed by nano-Fe3O4: Role of the interface

Abstract: h i g h l i g h t sCatechol or 4-chlorocatechol was removed within 3 h in nano-Fe 3 O 4 /H 2 O 2 system. 4-Chlorocatechol was removed faster than catechol, with a minor mineralization. The oxidation of (chloro-)catechols obeyed Eley-Rideal mechanism. Carboxyl acids and ethers or dimers were generated and also adsorbed on nano-Fe 3 O 4 . a r t i c l e i n f o /g. Almost all the catechol or 4-chlorocatechol was oxidized within 3 h after the addition of H 2 O 2 , while about only 10% of the parent compounds adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The strong band at 1261 cm −1 was assigned to ν(CO) of adsorbed catechol species, and the band at 1275 cm −1 was assigned to the combination of an ether C-O-C stretch between aromatic rings and the O-H bending vibration (Dubey et al, 1998;Lana-Villarreal et al, 2005), suggesting the formation of polymeric catechol species during the oxidation. The IR results were consistent with the results from previous work in which the formation of carboxylates, alcohols and dimers of catecholate species, such as 2-furanglycolic acid, 1,2-benzendicarboxylic acid and formic acid, oxalic acid, maleic acid and succinic acid, was identified for the oxidation of catechol by Fe 3 O 4 -H 2 O 2 , by GC-MS (Gas Chromatography-Mass Spectrometer), ESI-Q-TOF-MS and ion chromatography analysis (He et al, 2014).…”
Section: Surface Speciation During Oxidation Of Catecholsupporting
confidence: 79%
“…The strong band at 1261 cm −1 was assigned to ν(CO) of adsorbed catechol species, and the band at 1275 cm −1 was assigned to the combination of an ether C-O-C stretch between aromatic rings and the O-H bending vibration (Dubey et al, 1998;Lana-Villarreal et al, 2005), suggesting the formation of polymeric catechol species during the oxidation. The IR results were consistent with the results from previous work in which the formation of carboxylates, alcohols and dimers of catecholate species, such as 2-furanglycolic acid, 1,2-benzendicarboxylic acid and formic acid, oxalic acid, maleic acid and succinic acid, was identified for the oxidation of catechol by Fe 3 O 4 -H 2 O 2 , by GC-MS (Gas Chromatography-Mass Spectrometer), ESI-Q-TOF-MS and ion chromatography analysis (He et al, 2014).…”
Section: Surface Speciation During Oxidation Of Catecholsupporting
confidence: 79%
“…Nevertheless, other researchers propose that the surface-generated ROS mainly oxidize the organic compounds in solution, especially for unadsorbed organic compounds (Furman et al, 2009;Liang et al, 2012), i.e., an Eley-Rideal mechanism. He et al (2014) directly observed that adsorbed catechol or 4-chlorocatechol remained on the nano-Fe 3 O 4 surface during the oxidation by in-situ flow-cell ATR-FTIR experiments. Hence, ROS was hypothesized to predominantly attack the unadsorbed parent compounds near the interface region.…”
Section: Heterogeneous Catalysis Mechanismmentioning
confidence: 99%
“…Meanwhile, the activity of Fe 3 O 4 MNPs decreased gradually during consecutive runs, probably due to the leached iron and other factors, like the poisoning of the active catalytic sites by adsorbed organic species or oxidation of the surface (He et al, 2014) etc.…”
Section: +mentioning
confidence: 99%
“…The preparation of the Fe 3 O 4 film was prepared as our previous work [28]. The FTIR Spectra were acquired using the Nicolet 8700 FTIR spectrometer (Thermo, USA) equipped with a DTGS detector and ATR accessory, and were recorded by averaging 32 scans at a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%